HIV PrEP is more than ART‐lite: Longitudinal study of real‐world PrEP services data identifies missing measures meaningful to HIV prevention programming. Issue 10 (14th October 2021) - Reed, Jason Bailey; Shrestha, Prakriti; Were, Daniel; Chakare, Tafadzwa; Mutegi, Jane; Wakhutu, Brian; Musau, Abednego; Nonyana, Nyane Matebello; Christensen, Alice; Patel, Rupa; Rodrigues, Jessica; Eakle, Robyn; et al.
Abstract: Introduction: Evidence indicates HIV oral pre‐exposure prophylaxis (PrEP) is highly efficacious and effective. Substantial early discontinuation rates are reported by many programs, which may be misconstrued as program failure. However, PrEP use may be non‐continuous and still effective, since HIV risk fluctuates. Real‐world PrEP use phenomena, like restarting and cyclical use, and the temporal characteristics of these use patterns are not well described. The objective of our study was to characterize and identify predictors of use patterns observed in large PrEP scale‐up programs in Africa. Methods: We analysed demographic and clinical data routinely collected during client visits between 2017 and 2019 in three Jhpiego‐supported programs in Kenya, Lesotho and Tanzania. We characterized duration on/off PrEP and, using ordinal regression, modelled the likelihood of spending additional time off and identified factors associated with increasing cycle number. The Andersen‐Gill model was used to identify predictors of time to PrEP discontinuation. To analyse factors associated with a client's first return following initiation, we used a two‐step Heckman probit. Results: Among 47, 532 clients initiating PrEP, approximately half returned for follow‐up. With each increase in cycle number, time off PrEP between use cycles decreased. The Heckman first‐step model showed an increased probability of returning versus not by older age groups and among key and vulnerable population groups versus the general population; in the second‐step model older age groups and key and vulnerable populations were less likely in Kenya, but more likely in Lesotho, to return on‐time (refill) versus delayed (restarting). Conclusions: PrEP users frequently cycle on and off PrEP. Early discontinuation and delays in obtaining additional prescriptions were common, with broad predictive variability noted. Time off PrEP decreased with cycle number in all countries, suggesting normalization of use with experience. More nuanced measures of use are needed than exist for HIV treatment if effective use of PrEP is to be meaningfully measured. Providers should be equipped with measures and counselling messages that recognize non‐continuous and cyclical use patterns so that clients are supported to align fluctuating risk and use, and can readily restart PrEP after stopping, in effect empowering them further to make their own prevention choices.